Text Mining on Product Blurbs: Reward Consumption in Cosmetics during the COVID-19 Lockdowns in the UK - Lu, Ying-Shiou (2022)
Covid-19 has triggered an evolutionary change in the business environment and consumer behaviours. During the outbreak of the pandemic, people were suddenly trapped in their homes. Thus, the demand for online shopping has been accelerated. When people shop online, product descriptions serve as a primary source of information to know the products. A good product description supplies clear information on the features of the product but also intrigues consumers’ interest. Hence, product blurbs have become an unneglectable attribute in marketing strategy. This study investigates product blurbs using text analytics and machine learning techniques to inspect the difference in trends in consumers’ preferences for luxury products in pre-pandemic and during the pandemic periods. Besides, this study also examines the relationship between the luxury consumption ratio and the deprivation level of each region in England by incorporating the IMD data (Index of Multiple Deprivation) released by the UK government. The results indicate that there is a downward trend in the luxury consumption of beauty products during the lockdowns in the UK. Furthermore, we find that even though the general ratio of luxury consumption experienced a distinctive dip during lockdowns, areas deemed to be more deprived demonstrated a stronger intention for luxury consumption compared with less deprived areas. Based on the findings, recommendations for marketers are provided in response to the trends we observed in this research.